PERANAN PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UPPKS) TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN CIASEM, KABUPATEN SUBANG - Dian Hakip Nurdiansyah; Gusganda suria manda (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
Globalization has impacted ons the presence of rapid change of social wealth and also higher poverty. This has driven many institutions to reduce the level of poverty. To do so, iti conducted through the implementation of family empowerment program as developed by BKKBN through a program for increasing the income of family welfare (UPPKS). UPPKS has a goal to improve family income and welfare through family planning as their members. This study used quantitative methods design through survey methods. It used survey collected from respondents using questionnaires. The results showed that the implementation of the program in the UPPKS of Ciasem district has proven effectively can increase income rate and family welfare. The program participants use the program as the capital for small industry, Agroindustry and livestock. Keywords : UPPKS program, Family Planning, poverty